Therapeutic and nutraceutical potential of edible Mushrooms: an overview (International Journal of Food and Nutritional Sciences, 2023)
In every country in the globe, mushrooms are valued for their therapeutic and dietary benefits. Because immunity and cellular protection are significant issues for health-conscious customers and for people who are coping with major health issues, and increasing vegetarians’ interest in mushrooms has reached a height. Mushrooms typically belong to the Basidiomycetes family, which contains a wide variety of mushroom species and compounds with medicinal and nutritional value. According to reports, they are the most beneficial in people health and nutrition around the world. Around the world, studies on the medicinal and dietary benefits of mushrooms are in progress. Important information is being provided by researchers on the variety of bioactive substances present in these intriguing fungi. Mushrooms are now more widely accepted as a food and dietary supplement. Research on the bioactive metabolites/phytoconstituents of mushrooms is currently being actively conducted by numerous academic and research institutions. The current research intends to evaluate the variety of mushrooms and its benefits in the modern era, i.e., the types of metabolites/phytoconstituents present in these mushrooms, particularly those with medicinal and nutraceutical value, free radical scavenging activities and their function as bioactive agents.